Terrorism in Southwest Papua Region as Asymmetric Warfare - Prasetyo, Soya Ani; Sutanto, Rudy; Cempaka T, Fauzia G (PT FORMOSA CENDEKIA GLOBAL, 2024)
War is an event that can be avoided by most countries in the world. War may be the last alternative that must be taken if diplomacy do not reach an agreement. One of the categories of warfare that results is the asymmetric warfare pattern, which has become a trend in the form of warfare in the current era. Asymmetric warfare describes modern conflicts that exploit power inequalities between the parties involved. It involves tactics and strategies that are different from conventional warfare. The Southwest Papua region has become the center of international attention in recent years due to the increasingly worrying escalation of the terrorist conflict. To understand the escalation of terrorism in Southwest Papua, we need to consider the long history of ethnic and political conflict in the region. Terrorism in Southwest Papua is not only a threat to security, but also an asymmetric war with significant long-term implications due to dissatisfaction and feelings of marginalization that have existed for decades. This article also refers to data and case studies to provide a deeper understanding of terrorism in the Southwest Papua region and its relevance within the framework of asymmetric warfare. The research method in this writing uses a library study method which will be obtained from library sources such as books, websites, articles, journals, and so on. It is hoped that the results of this research will provide an understanding of the causes of terrorism in the Southwest Papua region as asymmetric warfare occurred in Indonesia.